Immersive Reality Experience Technology for Reducing Social Isolation and Improving Social Connectedness and Well-being of Children and Young People Who Are Hospitalized: Open Trial - Hiran Thabrew; Laura A Chubb; Harshali Kumar; Christa Fouché (JMIR Publications, 2022)
BackgroundChildren and young people who are hospitalized can feel disconnected from their peers and families, which can, in turn, predispose them to psychological problems, including anxiety and depression. Immersive reality experience technology, recently developed by the New Zealand Patience Project Charitable Trust, may help to overcome these issues. Immersive reality experience technology uses immersive 360° live streaming and a virtual reality headset to enable children and young people who are hospitalized to connect through cameras located in either their school or home environment and via SMS text messaging with a designated buddy. ObjectiveThis trial aims to expand qualitative findings from a previous smaller proof of concept trial to ascertain the views of New Zealand children and young people who are hospitalized, their caregivers, and teachers regarding immersive reality experience technology and quantitatively evaluate the effectiveness of immersive reality experience technology in reducing social isolation and improving social connectedness and well-being using validated outcome measures. MethodsAn open trial of immersive reality experience technology was conducted between December 2019 and December 2020 for which 19 New Zealand children and young people aged 13 to 18 years who had been hospitalized at Starship Hospital-a specialist pediatric hospital in Auckland-for at least 2 weeks were recruited. All young people completed the Short Warwick-Edinburgh Mental Well-Being Scale, an abbreviated version of the Social Connectedness Scale, and the Social Inclusion Scale at baseline. Of the 19 participants, 10 (53%) used immersive reality experience technology as often as they wished over a 6-week period and completed postintervention measures. Semistructured interviews with a subset of the 10 young people, 4 caregivers, and 6 teachers were conducted immediately after the intervention. ResultsParticipants reported improvements in social inclusion (mean change 3.9, SD 2.8; P=.06), social connectedness (mean change 14.2, SD 10.0; P=.002), and well-being (mean change 5.7, SD 4.0; P=.001). Key themes from interviews with participants, caregivers, and teachers were the importance of support for using immersive reality experience technology, connecting versus connectedness, choice and connection, and the value of setting it up and getting it right. Recommendations for improving connectedness via immersive reality experience and related technologies were also provided. ConclusionsImmersive reality experience technology can improve the social inclusion, social connectedness, and well-being of New Zealand children and young people who are hospitalized. With some technological modifications and simplified implementation, immersive reality experience and related technology could become part of standard care and support children and young people who are hospitalized in New Zealand and elsewhere to sustain family and peer cohesion, experience fewer psychological problems, and more easily return to normal life following the completion of treatment. Trial RegistrationAustralian New Zealand Clinical Trials Network Registry ACTRN12619000252112; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=376837&isReview=true